2011
DOI: 10.1371/journal.pone.0018921
|View full text |Cite
|
Sign up to set email alerts
|

Mature Peripheral RPE Cells Have an Intrinsic Capacity to Proliferate; A Potential Regulatory Mechanism for Age-Related Cell Loss

Abstract: BackgroundMammalian peripheral retinal pigmented epithelium (RPE) cells proliferate throughout life, while central cells are senescent. It is thought that some peripheral cells migrate centrally to correct age-related central RPE loss.Methodology/Principal FindingsWe ask whether this proliferative capacity is intrinsic to such cells and whether cells located centrally produce diffusible signals imposing senescence upon the former once migrated. We also ask whether there are regional differences in expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 32 publications
7
42
0
Order By: Relevance
“…Ranbp2 is implicated in arresting mitotic progression (26,58,59), a process that is critical to support the repair capacity of the RPE, presumably due to differences in regenerative capacity between the central and peripheral RPE (70). Hence, we examined also changes of the proliferative capacity of the RPE at different ages between RPE-cre::Ranbp2 ϩ/ϩ and RPE-cre::Ranbp2…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ranbp2 is implicated in arresting mitotic progression (26,58,59), a process that is critical to support the repair capacity of the RPE, presumably due to differences in regenerative capacity between the central and peripheral RPE (70). Hence, we examined also changes of the proliferative capacity of the RPE at different ages between RPE-cre::Ranbp2 ϩ/ϩ and RPE-cre::Ranbp2…”
Section: Resultsmentioning
confidence: 99%
“…It is thought that the central RPE becomes senescent due to hyperplastic senile changes first proposed by Duke-Elder and Perkins (87), whereas the peripheral RPE retains repair capacity due to its competency to reenter the cell cycle (70). Although the molecular bases for the proliferative capacity of peripheral RPE are unresolved, they may arise from emmetropization, a coordinated process of development and growth of various tissues of the eye by mechanisms not yet elucidated (70,88).…”
Section: Rbd2/3*-hamentioning
confidence: 99%
See 1 more Smart Citation
“…The RPE monolayer, formed in the early embryo, is a terminally differentiated cell sheet that develops with a center to periphery gradient such that only the peripheral cells retain low levels of proliferation, whereas the remainder remains nonproliferative throughout life [39,40]. However, in culture, their normal quiescence can be released, resulting in a re-entry into the cell cycle accompanied by proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, when isolated and cultured in vitro the RPE has strong proliferative potential, while recent studies have shown that, even in vivo, adult peripheral RPE cells can proliferate. 90 In some conditions, RPE cell proliferation can be observed usually in association with significant degrees of inflammation such as uveitis, or prolonged retinal detachment. With age however, slowly progressive RPE cell death is the more likely outcome, most probably in the form of apoptosis (reviewed in Williams et al 77 ).…”
Section: Pathology Of Macular Degenerationmentioning
confidence: 99%